The Effect of Delayed Examination and Storage Conditions on Plasma Glucose Levels: Pengaruh Variasi Waktu Penundaan Pemeriksaan dan Kondisi Penyimpanan terhadap Kadar Glukosa Plasma - Nur Aini Hidayah Khasanah; Nanda Gusti Lidiatama; Nilasari Indah Yuniati; Fajar Husen (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
Blood glucose examination is an important parameter for screening and monitoring diabetes mellitus. The accuracy of glucose testing is influenced by pre-analytical factors, particularly delayed examination and specimen storage conditions. Delayed examination may cause a decrease in glucose levels due to ongoing glycolysis after blood collection. This study aimed to determine the effect of examination delay time and storage conditions on plasma glucose levels. This laboratory experimental study used a factorial design with repeated measures. The delay times consisted of 0, 2, and 4 hours, while the storage conditions included EDTA plasma stored at room temperature, EDTA plasma stored at 4ºC, and NaF plasma. Plasma glucose levels were measured using the GOD-PAP method. Data were analyzed using the Shapiro-Wilk test, Levene’s test, Two-Way ANOVA, and Tukey Post Hoc test. The results showed that plasma glucose levels decreased as the examination delay time increased. After 4 hours of delay inEDTA plasma at room temperature, glucose levels were reduced by 55.8%, EDTA plasma stored at 4ºC by 52.3%, and NaF plasma by 30.7%. There was a significant effect of variations in examination delay time and storage conditions on plasma glucose levels (p<0.005). It can be concluded that NaF plasma was more effective in maintaining glucose stability compared with EDTA plasma stored at room temperature or under refrigeration conditions.